New H2O–H2O collisional rate coefficients for cometary applications. Issue 4 (8th September 2020) - Boursier, C; Mandal, B; Babikov, D; Dubernet, M L
ABSTRACT: We re-introduce a semiclassical methodology based on theories developed for the determination of broadening coefficients. We show that this simple and extremely fast methodology provides results that are in good agreement with results obtained using the more sophisticate MQCT approach. This semiclassical methodology could be an alternative approach which allows to provide large sets of collisional data for very complex molecular systems. It saves time both on the determination of potential energy surfaces and on the collisional dynamical calculations. In addition, this paper provides more complete sets of rotational de-excitation cross-sections and rate coefficients of H2 O perturbed by a thermal average of water molecules. Those data can be used in the radiative transfer modelling of cometary atmospheres.